PENGETAHUAN LANSIA TENTANG HIPERTENSI SEBELUM DAN SESUDAH DIBERIKAN PENDIDIKAN KESEHATAN DENGAN VIDEO DI DESA SURADITA TAHUN 2015 - Ilmi; Royani (Jurnal Kesehatan STIKes IMC Bintaro, 2018)
Introduction, Knowledge is the result of a process to find out, from which was not knowing to knowing, of not be able to be able to. In the process of finding out, it covers a variety of methods and concepts, either through education or through experience. Hypertension or more commonly known as high blood pressure is a condition in which a person's blood pressure is above normal or optimal limit of 120 mmHg for systolic and 80 mmHg for diastolik.penelitian aims to see an increase in elderly knowledge about hypertension after being given health education with video. Research methods, this study uses the Pre Experimental Design One approach - group pretest-posttest design. Sempel decision to use non-random sampling with a sample of 36 elderly, for a measurement instrument using questionnaires, while statistically using the Wilcoxon test. Result, results showed sig (0,000) is smaller than α (0:05) so that Ha is accepted. Conclusion, the results of this study showed no significant difference between the knowledge of hypertension before and after health education. Recommendation, the results of this study recommends further research with video method has increased from not knowing to knowing.